PENGEMBANGAN BANK WAKAF MIKRO DI PONDOK PESANTREN BUDHI DHARMA PIYUNGAN BANTUL - Ayif Fathurrahman (LPPM ITB AAS Indonesia Surakarta, 2023)
The problem of partners who are appointed in this community service program is the development of the potential of Islamic boarding schools as the economic center of the community. In relation to the main problem, this community service program has offered a solution that is expected to solve partner problems. Thus, PKM activities are held to empower the community around the Islamic boarding school environment through the establishment of a sharia-based microfinance institution (LKM Syariah)/Micro Waqf Bank (BWM) with a mentoring pattern. The objectives of the Micro Waqf Bank program are: 1). Maximizing the role of pesantren in the empowerment program for the productive poor. 2). Build and strengthen socio-economic institutions from Islamic boarding schools for the environment around Islamic boarding schools in the form of professional, accountable, and independent Sharia LKMs through the growth of Community Business Groups Around Indonesian Islamic Boarding Schools (KUMPI). The results and outputs of the activities after the socialization and mentoring were carried out first, increasing knowledge and understanding of sharia economics comprehensively to students regarding entrepreneurship. Second, confirming the Islamic boarding school as an entrepreneurial boarding school based on sharia economics. Third, to empower communities around Islamic boarding schools through the establishment of sharia-based microfinance institutions (LKM Syariah)/Micro Waqf Banks (BWM) with a mentoring pattern.